Penggunaan Energi Listrik Warga Fis dalam Mewujudkan Pilar Energi Bersih di Kampus Unnes Tahun 2018 - Sholekhah, Siti Nur Fatimah; Setyowati, Dewi Liesnoor (Edu Geography, 2019)
The purpose of this study was to determine the understanding of the FIS residents in the use of electrical energy, knowing the concerns of the leaders and managers of the FIS campus about electricity. The population in this study were leaders, facilities and infrastructure managers, lecturers, education staff and students. Sampling used stratified random sampling technique with the sample total of 99. Data collection techniques used were observation, tests, questionnaires and interviews. The results of this study indicate that FIS citizens' understanding includes high knowledge (72.0%), The attitude of citizen’s of 49,9% agreed with the existence of policies and appeals in saving electricity, and the behavior of FIS citizen’s 41,0% often made electricity savings on campus. The concern of the leaders and managers regarding the saving of electricity is the making of SOPs for the use of electrical equipment, the replacement of lamps in the FIS environment into LED lights, and the installation of air conditioners in certain rooms. Commitments given by the leadership are in accordance with the objectives, principal and function of the mandate given. Tujuan dari penelitian ini untuk mengetahui pemahaman warga FIS dalam penggunaan energi listrik, mengetahui kepedulian pimpinan dan pengelola kampus FIS tentang energi listrik. Populasi dalam penelitian ini adalah pimpinan, pengelola sarana prasarana, dosen, tenaga kependidikan dan mahasiswa. Pengambilan sampel menggunakan teknik stratified random sampling dengan total sampel 99. Teknik pengumpulan data yang digunakan adalah observasi, tes, angket dan wawancara. Hasil penelitian ini menunjukkan bahwa pemahaman warga FIS yang meliputi pengetahuan tinggi (72,0%), sikap warga FIS 49,9% setuju dengan adanya kebijakan dan himbauan dalam penghematan listrik, serta perilaku warga FIS 41,0% sering melakukan penghematan listrik dikampus. Kepedulian pimpinan dan pengelola kaitannya penghematan energi listrik yaitu pembuatan SOP penggunaan peralatan listrik, penggantian lampu di lingkungan FIS menjadi lampu LED, serta pemasangan AC diruangan tertentu.